The association between farm-level antimicrobial usage and resistance of Staphylococcus spp., as the major genus isolated from aerosol samples, in Japanese piggeries - Kobayashi, Sota; Tamamura-Andoh, Yukino; Yamane, Itsuro; Kusumoto, Masahiro; Katsuda, Ken (Frontiers in Veterinary Science, 2023)
Bacteria are the dominant particulate matter in livestock houses and can threaten animal and public health. Antimicrobial resistance (AMR) is a crucial concern worldwide, and nationwide measures established based on the One Health approach are being implemented in many countries. This requires multidisciplinary perspectives and collaboration among the human, animal, and environmental sectors. However, information on the AMR risk in livestock house aerosol is limited, especially its association with antimicrobial usage (AMU). Therefore, this study was conducted to reveal the AMR profile of Staphylococcus, the major bacterial genus in the aerosol of the piggeries of Japanese farms, and the association between farm-level AMU and AMR. The investigation at 10 farrow-to-finish pig farms revealed that regardless of the sampling season and the piggery group, the resistance rate of isolated staphylococci for oxacillin, erythromycin, and lincomycin was more than 40% of the median and tended to be higher than that for other antimicrobials. The AMU adjusted by the defined daily dose (DDD-adjusted AMU) in the fattening piggery group was significantly higher than that in the sow piggery group (P < 0.05). Finally, for the fattening piggery group, the generalized linear mixed model revealed that the AMR rate for oxacillin, erythromycin, tetracycline, and chloramphenicol was positively associated with the corresponding class-based DDD-adjusted AMU of penicillins (odds ratio (OR) = 2.63, P = 0.03), macrolides (OR = 6.89, P = 0.0001), tetracyclines (OR = 2.48, P = 0.04), and amphenicols (OR = 3.22, P = 0.03), respectively. These significant positive associations observed in this study imply that the resistance rate for these antimicrobials may decrease by reducing the corresponding antimicrobials' use. In addition, the resistance rates for erythromycin and chloramphenicol also displayed a positive association with the Bacterial profile of piggery aerosol 2 AMU of antimicrobial classes other than macrolides and amphenicols, respectively. The mechanism underlying these phenomena is unclear; therefore, further evaluation will be needed. As limited studies have reported staphylococci in piggery aerosol and its AMR with quantitative AMU, these results based on on-farm investigations are expected to aid in establishing countermeasures for AMR of aerosol bacteria in pig farms.